pengembangan modul elektronik berbasis android menggunakan aplikasi sigil sebagai media pembelajaran - Ajeng Rahma Sudarni (Universitas Negeri Padang, 2023)
Abstract— This study aims to develop digital simulation learning modules and produce valid, practical and effective digital simulation learning modules. This research is a development research. The model chosen in this study is a 4-D model: define, design, develop, and disseminate. The subject was 10th grade students of the Genus Health Vocational School. The type of data used is primary data. The instruments used to collect data in this study were instruments of validity, practicality, and effectiveness. The research data were analyzed by descriptive statistics. Data were obtained through questionnaires from validators and student response questionnaires as well as teacher response questionnaires to the developed e-module. The results of the validity test analysis to media experts obtained a validation value of 0.84, so the android-based learning e-module was categorized as valid. Furthermore, the validation results from material experts obtained a validation value of 0.85, meaning that the material in the Android-based learning e-module is categorized as valid. The results of the practicality of Android-based E-Modules for teachers obtained an average of 82.3 with very practical categories, and students obtained an average of 85 with very practical categories. The results of classical completeness scores obtained that 20 students completed with a percentage of 93.67%, it was concluded that the android-based e-module media was said to be effective from a review of students' classical scores. The effectiveness of the product on learning outcomes based on classical completeness which reached 93.67% and the gain score value of 0.32 in the medium category, it can be concluded that the android-based learning e-module is declared effective.